2017
DOI: 10.1017/s0022377817000605
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless microinstabilities in stellarators. Part 4. The ion-driven trapped-electron mode

Abstract: Optimised stellarators and other magnetic-confinement devices having the property that the average magnetic curvature is favourable for all particle orbits are called maximum-J devices, and have recently been shown to be immune to trapped-particle instabilities driven by the density gradient. Gyrokinetic simulations reveal, however, that another instability can arise, which is also associated with particle trapping but causes less transport than typical trapped-electron modes. The nature of this instability is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…The first one of these cases holds in a maximum-J stellarator and implies that ordinary density-gradient-driven trapped-electron modes are linearly stable. Proll et al (2012) and Helander, Proll & Plunk (2013) concluded that any collisionless instability must then draw energy from the ions rather than the electrons, and Plunk, Connor & Helander (2017) showed that there is indeed a remnant ion-driven trapped-electron mode if η i > 0. From our considerations of the available energy, this is not surprising, since it is apparently impossible to achieve a non-trivial ground state for both species simultaneously in the ordering (1.5).…”
Section: P Helandermentioning
confidence: 99%
“…The first one of these cases holds in a maximum-J stellarator and implies that ordinary density-gradient-driven trapped-electron modes are linearly stable. Proll et al (2012) and Helander, Proll & Plunk (2013) concluded that any collisionless instability must then draw energy from the ions rather than the electrons, and Plunk, Connor & Helander (2017) showed that there is indeed a remnant ion-driven trapped-electron mode if η i > 0. From our considerations of the available energy, this is not surprising, since it is apparently impossible to achieve a non-trivial ground state for both species simultaneously in the ordering (1.5).…”
Section: P Helandermentioning
confidence: 99%
“…2016; Helander, Proll & Plunk 2013; Plunk et al. 2014; Plunk, Connor & Helander 2017; Plunk et al. 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence in magnetised plasmas is usually generated by temperature and density gradient driven electrostatic microinstabilities, the most important ones being the ITG, electron temperature gradient (ETG) and trapped electron mode (TEM) (Doyle et al 2007). Their respective role for turbulence and transport has been explored analytically and by means of gyrokinetic simulations for stellarators and W7-X in particular (Proll et al 2012;Proll, Xanthopoulos & Helander 2013;Proll et al 2016;Helander, Proll & Plunk 2013;Plunk et al 2014;Plunk, Connor & Helander 2017;Plunk et al 2019). Besides gyrokinetic simulations with codes like GENE (Jenko et al 2000), key tools on W7-X to investigate turbulence in the core of the plasma experimentally are diagnostics like phase contrast imaging (PCI) (Edlund et al 2018;Huang et al 2021) and Doppler reflectometry (DR) (Carralero et al 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…The neoclassical transport induced by the bounce-averaged radial drift of trapped particles is strongly reduced. The magnetic field strength and the local curvature κ are shifted with respect to each other, and the turbulent structure can be distinguished between the ion-temperature gradient (ITG) and trapped-electron mode (TEM) by examining the scale length of the turbulence [18].…”
Section: Introductionmentioning
confidence: 99%